Fixing the emissions trading scheme: Carbon price stability in the EU and China. Issue 3 (22nd March 2019) - Boute, Anatole; Zhang, Hao
Abstract: This paper critically questions the legal and economic foundation of price regulation in environmental markets, with a focus on the European Union (EU) and Chinese Emissions Trading Schemes (ETSs). In 2018, the EU adopted a structural reform of its own ETS with the objective of increasing and stabilising carbon prices. This reform raises fundamental questions concerning the free market nature of the ETS and its function as a driver of low‐carbon investments. On the one hand, regulatory adjustments are necessary to address the large surplus of allowances that can result from exogenous shocks (e.g. economic downturn). On the other hand, the risk of regulatory intervention in the market undermines investor certainty. In China, limited regulatory independence and more stringent government control over the market exacerbates the threat posed by price control measures to the integrity of China's ETS and its role as a driver of investments in environmental protection.